Increased functional connectivity between the default mode and salience networks in unmedicated adults with obsessive‐compulsive disorder. Issue 2 (23rd September 2016) - Posner, Jonathan; Song, Inkyung; Lee, Seonjoo; Rodriguez, Carolyn I.; Moore, Holly; Marsh, Rachel; Blair Simpson, H.
Abstract: Deficits in attention have been implicated in Obsessive‐Compulsive Disorder (OCD), yet their neurobiological bases are poorly understood. In unmedicated adults with OCD ( n  = 30) and healthy controls ( n  = 32), they used resting state functional connectivity MRI (rs‐fcMRI) to examine functional connectivity between two neural networks associated with attentional processes: the default mode network (DMN) and the salience network (SN). They then used path analyses to examine putative relationships across three variables of interest: DMN‐SN connectivity, attention, and OCD symptoms. In the OCD compared with healthy control participants, there was significantly reduced inverse connectivity between the anterior medial prefrontal cortex (amPFC) and the anterior insular cortex, regions within the DMN and SN, respectively. In OCD, reduced inverse DMN‐SN connectivity was associated with both increased OCD symptom severity and decreased sustained attention. Path analyses were consistent with a potential mechanistic explanation: OCD symptoms are associated with an imbalance in DMN‐SN networks that subserve attentional processes and this effect of OCD on DMN‐SN connectivity is associated with decreased sustained attention. This work builds upon a growing literature suggesting that reduced inverse DMN‐SN connectivity may represent a trans‐diagnostic marker of attentional processes and suggests a potential mechanistic account of the relationship between OCD and attention. Reduced inverse DMN‐SN connectivity may be an important target for treatment development to improve attention in individuals with OCD. Hum Brain Mapp 38:678–687, 2017 . ©2016 Wiley Periodicals, Inc.